Study on the Adjustment Strategies of Businesses in the Retail Industry after the COVID-19 Pandemic - Chen Zhijing (SHS Web of Conferences)
At the start of 2020, the mysterious coronavirus, COVID-19, started its journey in Wuhan, China. It quickly spread across China due to the massive transportation during the Chinese New Year. The virus then takes opportunities to get into Asia and later the whole world. Lots of people, with no prior knowledge to protect themselves, got infected, and many of them died due to its serious complications. This created problems for every industry as lockdowns were happening and lots of transaction opportunities were blocked. This investigation, mainly conducted by diving deep into a real-world business and reflects on its performance, aims to point out effective changes in marketing strategies for companies in the retail sector after COVID-19, hopefully helping them to adjust their focus and follow up with new changes. Strategies that companies could use include a shift of focus from offline to online, specifically in advertising and shopping, promotions, and local supply chains.